2013
DOI: 10.1016/j.pain.2013.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Self-management intervention for chronic pain in older adults: A randomised controlled trial

Abstract: This study compared an outpatient pain self-management (PSM) program, using cognitive-behavioural therapy and exercises, with 2 control conditions in 141 chronic pain patients aged > 65 years. Results immediately posttreatment indicated that relative to the Exercise-Attention Control (EAC) group, the PSM group was significantly improved on measures of pain distress, disability, mood, unhelpful pain beliefs, and functional reach. The mean effect size for these gains was 0.52 (range: 0.44-0.68). By 1-month follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
143
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(157 citation statements)
references
References 50 publications
7
143
1
4
Order By: Relevance
“…More encouraging results were achieved in a more recent study by Nicholas and colleagues (6). They showed that in people age 65 and older (n = 141), cognitive behavioral therapy (CBT) plus exercise, relative to an exercise attention control, produced significant improvements in pain-related distress, disability, and physical performance at post treatment and a one-month follow-up.…”
Section: Introductionmentioning
confidence: 95%
“…More encouraging results were achieved in a more recent study by Nicholas and colleagues (6). They showed that in people age 65 and older (n = 141), cognitive behavioral therapy (CBT) plus exercise, relative to an exercise attention control, produced significant improvements in pain-related distress, disability, and physical performance at post treatment and a one-month follow-up.…”
Section: Introductionmentioning
confidence: 95%
“…General health issues in an older population of chronic pain patients may compound the self-management of chronic pain. Nicholas et al [40] showed that in older chronic pain adults combining cognitive behavioral therapy based pain self-management and exercise was more effective than just the exercise alone.…”
Section: Discussionmentioning
confidence: 99%
“…The changes that occur in chronic pain to the entire central nervous system and brain do not differentiate in any way between, for instance, the individual with diagnosed osteoarthritis or the individual with joint pain but no X-ray findings, nor between the individual with celiac disease and another with irritable bowel syndrome. 48 Although much research and clinical effort have focused on adults of working age with chronic pain, CBT has been applied to help children 18,49 and older adults, 50 and to those with pain at the end of life. [51][52][53][54] We suspect that clinicians and researchers will continue to apply the general principles of CBT to a wide range of pain-related disorders.…”
Section: Likely Developments and Challengesmentioning
confidence: 99%